Influence of PMA on the anti-scuffing properties of AW/EP additives - Ueda,M; Kadiric,A; Spikes,H (Tribology International, 2022)
Scuffing is becoming a quite common failure mode in gears and bearings. It has been shown that AW/EP additives are effective in preventing scuffing, but only if they are able to form a thick tribofilm before encountering severe scuffing-type conditions. This study has employed a contra-rotating, step-sliding speed scuffing test to explore the impact of PMAs on the ability of ZDDP and a commercial SP additive-containing package to prevent scuffing when subjected to immediately severe conditions. It is found that some PMAs can greatly enhance the anti-scuffing performance of these AW/EP additives. They do this by forming thick, adsorbed boundary films that can withstand high speed sliding conditions and protect the rubbing surfaces long enough for tribofilms to form.